TREATMENT OF SORE THROAT IN CHILDREN OVER 5 YEARS OF AGE - T. A. Grechukha; M. G. Galitskaya (Union of pediatricians of Russia, 2013)
Sore throat is a frequent complaint of children. Another aspect considered in this article is the issue of untimely and groundless prescription of antibacterial therapy to children, as it may result both in allergic reactions and toxic effect on the body in whole. Children of all age groups are rather sensitive to pain. In case of an acute complaint, there must be an effective drug, which may safely be used in children. The article examines various pharmaceutical forms of drugs for sore throat treatment and appraises their advantages, disadvantages and usability in children over 5 years of age in detail.